A Case of Phosphoglyceride Crystal Deposition Disease in the Pelvic Soft Tissues Recurring after Initial Surgery. (11th February 2015) - Yamada, Yuki; Nishioka, Kazuhiro; Kajihara, Hirotaka; Noguchi, Taketoshi; Naruse, Katsuhiko; Horie, Kiyoshige
Abstract : Phosphoglyceride crystal deposition disease (PGDD) is a rare disease entity that is characterized by phosphoglyceride crystal deposition that stimulates the formation of masses in soft tissue scars or bones. We report a case of PGDD in the pelvic soft tissues that recurred after initial surgical treatment. A 50-year-old woman was referred to our hospital for the evaluation of pelvic masses that were observed on an abdominal ultrasound. Magnetic resonance imaging (MRI) revealed masses in the pelvic region, with the largest being 10 cm in diameter. The masses were diagnosed as ovarian malignant tumors, and an exploratory laparotomy was performed. Operative findings revealed them to be foreign body granulomas, and the patient was diagnosed with PGDD. The patient had a history of cesarean delivery at the age of 24 years. PGDD is extremely rare, but it should be considered in the differential diagnosis of abdominal masses in patients with a history of abdominal surgery.